Impact of the changing European Union regulations on Estonian accounting policies. Euroopa finantsaruandluse muudatuste sobivus Eestis - Güldenkoh, Maret; Silberg, Uno (Estonian Discussions on Economic Policy, 2014)
Financial reporting and audit activities are the areas to ensure the legitimacy of the everyday economic activities of the accounting entities. Financial reporting provides information on the past periods of the accounting entities; the audit activity is used to verify the accuracy of the recorded information and an assessment is given to the financial position of the audited entities. Auditing of financial statements prepared on the basis of historical financial information, results in increased reliability of the economic environment and stability of the financial environment of the state. The objective of this research was to assess the suitability of the European Union reporting principles for the auditing activity in Estonia. This objective was achieved with the following research tasks: 1) to provide an overview of the legal framework of the EU financial reporting and auditing activities; 2) to assess the problems related to the transposition of the legal framework in Estonia. The article consists of two parts, the first part provides an overview of the regulation of financial reporting and auditing activities in the European Union. The second part assess the impact of the European Union legislation on financial reporting and audit activities for the activities of the corresponding areas in Estonia. The research method used was a combined method, in the course of which legal acts were collected and analyzed, analysis of the data obtained from the commercial register was carried out and the impact of the Directive 2013/34 / EC to the accounting area of Estonia was assessed. Upon application of the Directive 2013/34/EU to the Estonia's legal framework, one cannot be sure that the desired administrative burden is reduced, rather it could bring along growth of the administrative burden for the accounting entities, which comprises the obligation of submission of additional reporting to various authorities. The reporting process could become more time-consuming. The decline in reporting volume could present a risk to the transparency and sustainability of the economic environment. Rather than reducing administrative burdens that are the goal of Directive 2013/34/EU, in Estonia the effect is just the opposite. The implementation of the Directive will result in an increase of the administrative burden and the obligation of duplication of reporting, which in turn can lead to a lack of transparency in the economic environment. The accounting entities will fail to submit the financial reports to the register on a timely manner, which in turn puts into question the information contained in the reports. Establishment of the audit limits would result in a reduction in the auditing obligation, an estimated 97-99% of entrepreneurs will remain unaudited.